2015
DOI: 10.4081/ija.2015.642
|View full text |Cite
|
Sign up to set email alerts
|

Annual effects of different organic fertilisers in a baby leaf crops system under tunnel in Southern Italy

Abstract: In a farm devoted to the production of fresh-cut leafy vegetables located in Eboli (Salerno), it was carried out a trial to compare the effects on crops and soil organic carbon (SOC) of biowaste compost, olive pomace compost, buffalo manure applied to soil in two doses (15 and 30 t ha<sup>−1</sup> fresh weight). The amendments were tested in order to start in defining a feasible strategy for the recovery/maintenance of soils in degradation due to the organic matter depletion triggered by the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Soil treatment with compost from olive pomace resulted in a lower Swiss chard growth than the other two composts, probably due to the higher C/N ratio (see Table 2) that determined a higher N immobilization in soil, a higher N competition in plants and soil microorganisms and a lower N availability for plant growth. According to this hypothesis are the results of Morra et al [39], who found a higher quickness of buffalo manure amendment than biowaste and olive pomace compost in supplying mineral nitrogen to a rocket crop. Our hypothesis is also supported by previous findings of Garcia-Ruiz et al [40].…”
Section: Plant Growthmentioning
confidence: 92%
“…Soil treatment with compost from olive pomace resulted in a lower Swiss chard growth than the other two composts, probably due to the higher C/N ratio (see Table 2) that determined a higher N immobilization in soil, a higher N competition in plants and soil microorganisms and a lower N availability for plant growth. According to this hypothesis are the results of Morra et al [39], who found a higher quickness of buffalo manure amendment than biowaste and olive pomace compost in supplying mineral nitrogen to a rocket crop. Our hypothesis is also supported by previous findings of Garcia-Ruiz et al [40].…”
Section: Plant Growthmentioning
confidence: 92%
“…Therefore, an amount of organic C of 7.6-8.1-8.2 t ha -1 with BMR 201, BMR 333 and Goliath, respectively, was tilled in the ground. These considerable quantities are comparable to the 7-8.5 t ha -1 of C introduced with 22-27 t ha -1 DM of biowaste or olive pomace composts, respectively, in the experiment carried out by Morra et al (2015) in a baby leaf crop system under greenhouse. N recovered from soil and fixed in sorghum plants ranged from 330 to 406 kg ha -1 .…”
Section: Site Of San Marzano Sul Sarnomentioning
confidence: 60%
“…the increase of SOC per unit of input) of compost or crop residues decreases with the amount added as shown in medium and long-term experiments by Pagano et al (2008) and Heitkamp et al (2012), respectively. Recently, experiments were carried out in fresh-cut leafy vegetables crop systems under tunnels in Sele river Valley by using olive husk compost, biowaste compost or buffalo manure as organic conditioners (Morra et al, 2013(Morra et al, , 2015. Tests were carried out for one or two years (two-year data not yet published) without modifying the soil tillage regime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first amendment, in 2013/2014, the sequence rocket-rocket-basilrocket was followed while in 2014/2015, after the second amendment, a rocket-rocket sequence was pursued. Productive and qualitative results related to the first year of the experiment were presented in Morra et al [28]. In this paper, which considers the second year, we focus on the last, major rocket cycle, which occurred in the cycle from November 2014 to April 2015.…”
Section: Experimental Design and Crop Managementmentioning
confidence: 99%